Etika Profesi Jaksa dalam Penegakan Hukum di Indonesia - Stepi Ayu; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Professional Ethics of Prosecutors in Law Enforcement in Indonesia Is a guideline for behavior in a Prosecutor profession, which if it can be implemented in accordance with the objectives will produce prosecutors who do have good moral qualities in carrying out their duties. So that the judicial life in our country will lead to success. The purpose of this writing is to find out and understand the regulation of the Prosecutor's Code of Ethics in the legal system in Indonesia and how the sanctions and procedures for resolving prosecutors who violate the code of ethics. This research was conducted with a Normative Juridical legal approach. The results of this writing: First, the regulation of the Prosecutor's Code of Ethics in the legal system in Indonesia is regulated in PERJA No. PER-014 / A / JA / 11/2012 concerning the Prosecutor's Code of Conduct, the Prosecutor's Code of Ethics is used as a direction or behavioral guide to realize Prosecutors who have integrity, are responsible, and guarantee the moral quality of Prosecutors in society in order to realize an effective, efficient, clean, transparent and accountable bureaucracy based on Tri Krama Adhyaksa. Second, Sanctions and Settlement Procedures for Prosecutors who violate the code of ethics. In the event of a violation of the code of ethics by a prosecutor, there are Sanctions, both the Code of Ethics, other sanctions, namely disciplinary sanctions for civil servants if they violate the disciplinary regulations of civil servants and criminal sanctions if the act is a criminal act, and the party authorized to carry out the settlement starting from the examination stage to the verdict is the code of conduct council.